Trends in undiagnosed HIV prevalence in England and implications for eliminating HIV transmission by 2030: an evidence synthesis model. (October 2021) - Presanis, Anne M; Harris, Ross J; Kirwan, Peter D; Miltz, Ada; Croxford, Sara; Heinsbroek, Ellen; Jackson, Christopher H; Mohammed, Hamish; Brown, Alison E; Delpech, Valerie C; Gill, O Noel; Angelis, Daniela De
Summary: Background: A target to eliminate HIV transmission in England by 2030 was set in early 2019. This study aimed to estimate trends from 2013 to 2019 in HIV prevalence, particularly the number of people living with undiagnosed HIV, by exposure group, ethnicity, gender, age group, and region. These estimates are essential to monitor progress towards elimination. Methods: A Bayesian synthesis of evidence from multiple surveillance, demographic, and survey datasets relevant to HIV in England was used to estimate trends in the number of people living with HIV, the proportion of people unaware of their HIV infection, and the corresponding prevalence of undiagnosed HIV. All estimates were stratified by exposure group, ethnicity, gender, age group (15–34, 35–44, 45–59, or 60–74 years), region (London, or outside of London) and year (2013–19). Findings: The total number of people living with HIV aged 15–74 years in England increased from 83 500 (95% credible interval 80 200–89 600) in 2013 to 92 800 (91 000–95 600) in 2019. The proportion diagnosed steadily increased from 86% (80–90%) to 94% (91–95%) during the same time period, corresponding to a halving in the number of undiagnosed infections from 11 600 (8300–17 700) to 5900 (4400–8700) and in undiagnosed prevalence from 0·29 (0·21–0·44) to 0·14 (0·11–0·21) per 1000 population. Similar steep declines were estimated in all subgroups of gay, bisexual, and other men who have sex with men and in most subgroups of Black African heterosexuals. The pace of reduction was less pronounced for heterosexuals in other ethnic groups and people who inject drugs, particularly outside London; however, undiagnosed prevalence in these groups has remained very low. Interpretation: The UNAIDS target of diagnosing 90% of people living with HIV by 2020 was reached by 2016 in England, with the country on track to achieve the new target of 95% diagnosed by 2025. Reductions in transmission and undiagnosed prevalence have corresponded to large scale-up of testing in key populations and early diagnosis and treatment. Additional and intensified prevention measures are required to eliminate transmission of HIV among the communities that have experienced slower declines than other subgroups, despite having very low prevalences of HIV. Funding: UK Medical Research Council and Public Health England.